Plasma hepcidin in early-stage breast cancer patients: no relationship with interleukin-6, erythropoietin and erythroferrone. (2nd November 2015) - Ciniselli, Chiara Maura; De Bortoli, Maida; Taverna, Elena; Varinelli, Luca; Pizzamiglio, Sara; Veneroni, Silvia; Bonini, Chiara; Orlandi, Rosaria; Verderio, Paolo; Bongarzone, Italia
Abstract : Objective: Hepcidin-25 production is stimulated by systemic inflammation, and it interferes with iron utilization, leading to anemia. This study aimed to investigate the relationships between the plasma levels of hepcidin, interleukin-6 (IL-6), erythropoietin (EPO) and erythroferrone (ERFE) in patients with benign breast disease or cancer. Methods: Plasma samples from a cohort of 131 patients (47 with benign breast disease and 84 with breast cancer) were subjected to the evaluation of hepcidin, IL-6, EPO and ERFE using SELDI-TOF-MS or immunoassays. Results: An elevated hepcidin was observed in malignant breast tumors compared to benign ones. No correlation was observed between hepcidin and IL-6, EPO or ERFE. Conclusion: Since the study included a cohort of patients (87%) with breast cancers smaller than 2 cm, these results may support our previous evidence about the potential role of hepcidin in breast cancer disease.